Evaluasi Program Tahfidz Melalui Media Sosial di Yayasan Indonesia Berkah - Wajdi, Firdaus; Fauzia, Sifa; Hakam, Ahmad (Jurnal Studi Al-Qur'an, 2020)
The Tahfidz Online program is the flagship program of the Indonesia Berkah Foundation. This study aims to describe and evaluate the implementation of the Indonesia Berkah Foundation's Tahfidz Online program. This research is qualitative research with data collection techniques using observation, interviews and document analysis. The CIPP (context, input, process, product) evaluation model developed by Daniel Leroy Stufflebeam et al. was used as an evaluation reference. This study finds out that: In terms of the input component, it shows that musyrifah, curriculum, and infrastructure have met the criteria. However, there are notes on the input of students not meeting the criteria of intention because God also does not understand the knowledge of recitation and Arabic. In terms of the media process components and materials, they do not meet the criteria of interest and are arranged in a sequence that makes it easy for students, while the method and time have met the criteria. Keywords: Online Tahfidz Program, Evaluation of Education